HUBUNGAN ANTARA DISIPLIN BELAJAR DENGAN HASIL BELAJAR PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Sukmanasa, Elly (Universitas Negeri Semarang, 2016)
This research applies correlational and survey method to collect the data about the correlation between learning discipline and students’ learning outcome in Social Science subject. The finding shows that Ho : py = 0. It means there is no correlation between learning discipline (X) and learning outcome (Y). Ha : py > 0. It means there is a correlation between learning discipline (X) and learning outcome (Y). It can be concluded that there is a high correlation between learning discipline (X) and learning outcome (Y) 94%. The detail data are as follows: 1) the normal distribution of the two variables is Lcalculated < Ltable = 0,1208 < 0,1240. Therefore, the distribution of learning discipline and learning outcome is normal. 2) learning discipline and learning outcome is homogenous, it can be seen from the calculation Xcalculated<Xtable= 2,262 < 33,92. Thus the two variables are homogenous.. 3) there is a correlation between learning discipline and learning outcome on Social Science subject seen from the correlation coefficien value (r=0,967), the value of determination coefficient (r2=0,94). It indicates that the contribution of variable X and variable Y is 94% with the regresion Ŷ = -47+0,49